PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN LIMBAH KAKAO YANG BERNILAI EKONOMIS DI DESA SANGGARHORHO - Hutubessy, Josina Irene Brigetha; Witi, Ferdinandus Lidang; Apelabi, Gabriel Otan; Fowo, Kristono Yohanes (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Assistance and implementation of technological innovations in the use of cocoa waste in Sanggarhoro Village for the Batu Putih and Tau Si 2 farmer groups through the PMM – KKN 2024 program aims to develop villages (Thematic KKN), especially in Sanggarhorho Village in utilising economically valuable cocoa plant waste. This program was implemented through a series of training and mentoring involving 18 members of the Batu Putih farmer group and 21 members of the Tau Si 2 farmer group. The method used was Participatory Rural Appraisal (PRA), namely the active involvement of all parties involved, starting the activity by carrying out surveys, and interviews with village officials and farmer groups. The training material includes counselling and training on the use of cocoa waste (cocoa shells) as raw material for bokashi fertiliser and animal feed. Evaluation of PMM – KKN activities by providing pre-tests and post-tests increased knowledge about the use of cocoa waste as fertilizer, 67.29% of farmers understood the use of cocoa waste as fertilizer and 96% understood the use of cocoa waste as animal feed. As a follow-up step, regular assistance is provided to farmer group participants to ensure that the skills and knowledge obtained during the training can be applied optimally in the community.